Optimization Algorithm for Blockchain Data Storage and Retrieval Based on DHT - Xie, Zhijun; Zheng, Lijuan (EAI Endorsed Transactions on Scalable Information Systems, 2026)
INTRODUCTION: Each node keeps the identical block data in the decentralized, tamper-proof distributed ledger known as the blockchain.OBJECTIVES: A blockchain network's working time lengthens, the amount of data that nodes must preserve and synchronize increases noticeably.METHODS: This brings up significant storage performance difficulties. We have started a study from a blockchain data storage standpoint to address this storage performance issue. We propose a distributed hash table (DHT)-based blockchain data archiving approach by analyzing the redundancy state caused by every node in the current blockchain network containing the same data. The block data is introduced in three ways: archived data building, lookup, and interaction with the underlying chain.RESULTS: This is done to ensure that blockchain data is not lost and can be accessed. This reduces storage redundancy and satisfies the practical requirements of storage and access in the blockchain's initial application.CONCLUSION: Experiments on energy transaction data show that the technique suggested in this article has a considerably lower storage occupancy increase rate than fabric storage.
Keywords: Distributed Hash Table; Blockchain; Storage; Archiving; Network Nodes